2019
DOI: 10.3390/land8050079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cash Crop Suitability Assessment Using Parametric, AHP, and FAHP Methods

Abstract: Cash crops, which include eucalyptus, play an important role in Thailand in wood utilization. Consequently, cash crops have become a significant driving force in land use changes and low crop yield; thus, the development of an accurate cash crop suitability model is needed. The aim of this study is to evaluate the land suitability of cash crops, such as eucalyptus, which is based on Multi Criteria Decision Making (MCDM) in Nakhon Ratchasima Province in Thailand. Parametric, classical Analytical Hierarchy Proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…A trapezoidal fuzzy number can be denoted as a = l, m l , m u , u and the membership function is [141].…”
Section: Trapezoidal and Triangular Fuzzy Numbersmentioning
confidence: 99%
“…A trapezoidal fuzzy number can be denoted as a = l, m l , m u , u and the membership function is [141].…”
Section: Trapezoidal and Triangular Fuzzy Numbersmentioning
confidence: 99%
“…The most important question was Q25 in the Use Behavior: "I use Google Classroom for writing quizzes and submitting assignments behavior", and the last important one was Q4: "If I use Google Classroom, I will increase my chances of passing the course" part of the Performance Expectancy construct. It was known that FAHP with TpFN numbers was the generalization of FAHP with TFN numbers [60], also had a better rank according to the expert opinions. Also, based to the unified index for comparing fuzzy numbers TFN and TpFN [61], [60] was shown that the trapezoidal FAHP method is the most suitable one, as it provides the most accurate results when compared to other methods.…”
Section: Comparison Results For Questions Levelmentioning
confidence: 99%
“…It was known that FAHP with TpFN numbers was the generalization of FAHP with TFN numbers [60], also had a better rank according to the expert opinions. Also, based to the unified index for comparing fuzzy numbers TFN and TpFN [61], [60] was shown that the trapezoidal FAHP method is the most suitable one, as it provides the most accurate results when compared to other methods.…”
Section: Comparison Results For Questions Levelmentioning
confidence: 99%
“…The AHP considers a set of evaluation criteria and alternative options from which the best decision is made. It generates a weight for each criterion according to the decision maker's pairwise comparisons [87]. The higher the weight, the more critical the corresponding criterion [20].…”
Section: Analytical Hierarchy Processmentioning
confidence: 99%